2018
DOI: 10.1002/we.2258
|View full text |Cite
|
Sign up to set email alerts
|

Active tugger line force control for single blade installation

Abstract: Single blade installation is one of the methods for installing large wind turbine blades at an o shore site. During this installation, each blade is lifted by the main crane from the deck of an installation vessel or a transportation barge with blade root approaching the hub. The blade root is then bolted to the hub. The nal mating phase is critical and requires high precision. Tugger lines from the crane boom are connected to the suspended blade to reduce pendulum motions. The entire process is typically comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…To verify the performance of the controller, time-domain simulations were conducted for turbulent wind conditions, using a 6DOF system with aerodynamic loads on the blade calculated similarly as in Zhao et al (2018). It was found that the proposed actively-controlled tugger line system works well as tested with the simulation verification model (Ren et al, 2017). A comparison of the blade translational motions at the root with and without the active tugger line control was shown in Figure 6.…”
Section: Blade Motion Reduction For Final Connectionmentioning
confidence: 97%
See 2 more Smart Citations
“…To verify the performance of the controller, time-domain simulations were conducted for turbulent wind conditions, using a 6DOF system with aerodynamic loads on the blade calculated similarly as in Zhao et al (2018). It was found that the proposed actively-controlled tugger line system works well as tested with the simulation verification model (Ren et al, 2017). A comparison of the blade translational motions at the root with and without the active tugger line control was shown in Figure 6.…”
Section: Blade Motion Reduction For Final Connectionmentioning
confidence: 97%
“…Therefore, it is important to explicitly model these loads and estimate the induced responses as well as to control the blades during the final mating phase. In this section, we will summarize the work on blade installation analysis and control (Zhao et al, 2018;Verma et al, 2017;Ren et al, 2017), including the global response analysis and the local damage analysis due to contact/impact of the blade crosssections with surrounding structures.…”
Section: Installation Of Offshore Wind Turbine Bladesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fundamental principles adopted to achieve static stability, a floating platform can be classified into three primary concepts: a semisubmersible (Semi), a Spar buoy and a Tension Leg Platform (TLP). Many researchers have made great efforts to investigate the difference in the dynamic responses of a variety of floating wind turbine systems [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Research on intelligent marine operations are seeing increasing attention [5][6][7][8][9][10]. The typical objectives are to enhance the overall efficiency, ensure safety, broaden the operating window, and, ultimately, gain economic benefits.…”
Section: Introductionmentioning
confidence: 99%